2002
DOI: 10.1002/bem.10068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electromagnetic radiation of mobile phones on the central nervous system

Abstract: With the increasing use of mobile communication, concerns have been expressed about the possible interactions of electromagnetic radiation with the human organism and, in particular, the brain. The effects on neuronal electrical activity, energy metabolism, genomic responses, neurotransmitter balance, blood-brain barrier permeability, cognitive function, sleep, and various brain diseases including brain tumors are reviewed. Most of the reported effects are small as long as the radiation intensity remains in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
117
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(131 citation statements)
references
References 163 publications
0
117
0
9
Order By: Relevance
“…Various non-thermal effects of MP-emitted EMW on the central nervous system, including permeability of the blood-brain barrier, neuronal electrical activity, neurotransmitter balance, cognitive function and sleep, have recently been reviewed. 1,2 Sexual behavior is a continuum of separate but linked processes: libido, erection, ejaculation, orgasm, detumescence and refractory period. 3 Sexual behavior in the male is a good example of the mutual collaboration between the brain and the male genital system.…”
Section: Introductionmentioning
confidence: 99%
“…Various non-thermal effects of MP-emitted EMW on the central nervous system, including permeability of the blood-brain barrier, neuronal electrical activity, neurotransmitter balance, cognitive function and sleep, have recently been reviewed. 1,2 Sexual behavior is a continuum of separate but linked processes: libido, erection, ejaculation, orgasm, detumescence and refractory period. 3 Sexual behavior in the male is a good example of the mutual collaboration between the brain and the male genital system.…”
Section: Introductionmentioning
confidence: 99%
“…In principle it seems possible that epileptic individuals may be especially sensitive to the effects of RF radiation, given the electrochemical instability of the neuron circuits involved in the cerebral electrical storms responsible for their seizures [9]. In previous work [13], we have in fact shown that radiation of the type used by the Global System for Mobile communications (GSM) triggers seizures in rats in which a seizure-prone state analogous to epilepsy had been induced by subconvulsive doses of picrotoxin [14].…”
Section: Introductionmentioning
confidence: 98%
“…On the contrary, it is wellestablished that the CNS in general [9], and the cerebral cortex in particular [10,11], is sensitive to radio frequency (RF) radiation. A radiation intensity too low to affect other organs or systems could therefore have significant pathological effects on the CNS [12].…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of the nervous system in biological responses to RF-EMF is an extensively studied field [5,6] and lately, the implication of the peripheral nervous system in response to MMW has been highlighted, especially concerning modulation of the pain sensation [7].…”
Section: Introductionmentioning
confidence: 99%